2017
DOI: 10.3389/fpsyg.2017.00368
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Short-term Gated Audiovisual Speech Training for Improving Auditory Sentence Identification in Noise in Elderly Hearing Aid Users

Abstract: This study aimed to examine the efficacy and maintenance of short-term (one-session) gated audiovisual speech training for improving auditory sentence identification in noise in experienced elderly hearing-aid users. Twenty-five hearing aid users (16 men and 9 women), with an average age of 70.8 years, were randomly divided into an experimental (audiovisual training, n = 14) and a control (auditory training, n = 11) group. Participants underwent gated speech identification tasks comprising Swedish consonants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…If the V signal is not available, the AV simulation feeds back to A brain areas and facilitates the voice (A) identification of that person. Note that in our previous articles (Moradi et al 2013, 2017b; Lidestam et al 2014), the speakers in the gated tasks and the HINT were different. Our previous research indicates that the perceptual doping effect is independent of speaker idiosyncrasy, as only one exposure to AV speech stimuli (with the same or different speakers in the initial exposure and following the A speech task) is sufficient to obtain subsequent improvement in A speech identification.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…If the V signal is not available, the AV simulation feeds back to A brain areas and facilitates the voice (A) identification of that person. Note that in our previous articles (Moradi et al 2013, 2017b; Lidestam et al 2014), the speakers in the gated tasks and the HINT were different. Our previous research indicates that the perceptual doping effect is independent of speaker idiosyncrasy, as only one exposure to AV speech stimuli (with the same or different speakers in the initial exposure and following the A speech task) is sufficient to obtain subsequent improvement in A speech identification.…”
Section: Discussionmentioning
confidence: 64%
“…The extent to which the type of listening conditions (e.g., clear versus distorted) would affect the perceptual doping effect on word identification in sentences requires further research. Moradi et al (2017b) suggested that background noise (relative to a silent listening condition) may enhance the perceptual doping effect by focusing listeners’ attention (or cognitive effort) on the A and V components of a speech item, to form a coherent AV speech item from an incoming speech signal so as to map it to corresponding phonological or lexical representations. The data from gated consonants, gated vowels, and vowel duration discrimination tasks in the present study indicate a perceptual doping effect even in silence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations